Comparison of Usage between Voice Switching Communication System (Vscs) Direct Speech (Ds) Vsat (Very Small Aperture Terminal) System and Voip (Voice Over Internet Protocol) - Atmaka, Ekky Widha; Respati, Jalu; Wisnu H., Adhitya; Luthfia, Lulu (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
One of the ground-to-ground DS coordination communications that need to be adapted to use on an IP basis, hereinafter referred to as Voice over Internet Protocol (VoIP). However, to be fully used and also as a substitute for VSAT, VoIP needs to be analyzed and also compared reliability and Cost Benefit Analysis (CBA) with VSAT. This is needed so that it is known that the adjustment to the improvement and development of technology and the future plan is ready to be implemented and also has a positive impact on aviation safety, operations and finances. The purpose of this study was to determine the comparison between the use of DS VSAT system with VoIP. The method used in this study is a mixed-method, with the category of descriptive analysis and the final results/conclusions of the study using the calculation of the percentage of data collecting (reliability test) and the ratio of cost benefit analysis (literature/archive studies). The results of the reliability test for 1 (one) year in 2021 obtained results for VSAT 99.53%-100% and for VoIP 99.5%-100%, from these results concluded in 1 (one) year the reliability between DS VSAT system and VoIP is the same ( Note: in December 2021 on the DS VSAT system there was a failure so that the percentage generated for 1 (one) month was only 99.95%, while the DS VoIP system in June to December never failed (failures that occurred in February - May could be due to the transition period for new equipment) While the results of Cost Benefit Analysis (CBA) between the two are 55.85%, where the use of DS VoIP systems is more financially efficient (saving) than the use of DS VSAT systems.